A new characid fish, Moenkhausia aurantia (Ostariophysi: Characiformes: Characidae), from the upper rio Tocantins basin in Central Brazil - Bertaco, Vinicius A.; Jerep, Fernando C.; Carvalho, Fernando R. (Zootaxa, 2011)
A new characid species, Moenkhausia aurantia, is described from the upper portions of rio Tocantins basin, in the Chapada dos Veadeiros, Goiás State, central Brazil. The new species differs from its congeners by the combination of 3 or 4 scale rows below and 5 or 6 scale rows above the lateral line, 21–25 branched anal-fin rays, 33–35 lateral line scales, 2–4 maxillary teeth, one diffuse humeral spot, and caudal spot continuous to the longitudinal line which extends posteriorly over the middle caudal-fin rays. A key to identify Moenkhausia species describe from the Tocantins-Araguaia basin is provided.